Tingkat Adopsi Inovasi Ib (Inseminasi Buatan) Pada Peternak Sapi Potong Di Kecamatan Lalabata Kabupaten Soppeng Adoption Of Innovation Ai ( Artificial Insemination ) Breeder In - Angga Nugraha; Agustina Abdullah; Nurani Sirajuddin (Universitas Islam Balitar, 2016)
The purpose of this study was to determine the extent to which farmers in adopting the technology of artificial insemination by measuring the time it takes breeders from receipt of the information to be applied , the quality of AI ( Application and recommendation ) , and Area Applied IB in cattle . The research was conducted in August - September 2014 against 30 respondents from 30 populations breeders who use technology AI ( Artificial Insemination ) . Data were analyzed using descriptive statistics by using tables Distribution Frekuwensi results showed adoption rate of technological innovation Artificial Insemination ( AI ) in beef cattle farms in the district Lalabata Soppeng ie Stage time is needed breeders from the receipt of the information to be obtained on application High category in the sense of the ability of farmers to adopt an innovation has been rapid , stage area located on the application of Low Category this suggests that the broad application of the implementation of the AI in the district as a whole Lalabata the breeder has done these activities , but not all animals in peliharanya apply technology Artificial Insemination ( AI ) , and Phase AI quality is in the category Medium this suggests that the quality of AI in District Lalabata Soppeng ie almost entirely of farmers already know the signs of estrus in livestock before conducting AI. Keywords : Adoption Levels , Artificial Insemination , Beef Cattle Breeders